Teaching Ethical GenAI Use through Student-Led Discussions in EAP - Ngo, Thu Ngan; Hastie, David (St Andrews Journal of International and Language Education, 2025)
This paper explores a student-led discussion activity on GenAI use within an English for Academic Purposes (EAP) module, designed to foster critical thinking and ethical reasoning with regard to GenAI. Students analyse realistic scenarios illustrating appropriate and inappropriate GenAI use, aligning their decisions with academic integrity principles. Teachers’ observations showed strong student engagement, with students reflecting on their own GenAI use. Nuanced scenarios prompted the most meaningful debate, although balancing complexity and clarity proved a challenge. Although its impact on misconduct is difficult to measure, the activity shows potential for promoting responsible and ethical GenAI use in academic settings.